Evaluation of Anti-Cancer Activity of Momordica dioica using MTT and DAPI Assays - Waoo, Ashwini A. (Asian Journal of Pharmaceutics (AJP), 2025)
Aim: The aim of this study was to evaluate the anti-cancer potential of methanolic extracts from the stem-leaf, root, and callus of Momordica dioica against two cancer cell lines: Michigan Cancer Foundation-7 (MCF-7) (human breast cancer) and A549 (lung cancer). Materials and Methods: The evaluation was conducted using the 3-(4,5-Dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay and 4′,6-Diamidino-2- phenylindole (DAPI) staining method, which are reliable and widely used techniques in cancer research. The MTT assay, a sensitive and quantitative colorimetric method, assessed cell viability, proliferation, and metabolic activity. Results and Discussion: The results revealed that methanolic stem-leaf and callus extracts significantly inhibited the growth of MCF-7 cells at IC50 concentrations, indicating their effectiveness in targeting breast cancer cells. DAPI staining, a fluorescence-based method used to detect DNA fragmentation and apoptosis, was applied to the A549 lung cancer cell line. The findings demonstrated a dose-dependent induction of apoptosis in A549 cells treated with the extracts, suggesting their potential role in activating apoptotic pathways in lung cancer cells. Overall, these results highlight the promising anti-cancer properties of M. dioica methanolic extracts. Conclusion: The plant extract can inhibit cancer cell growth and induce apoptosis, underscoring their potential as natural therapeutic agents. This study provides a foundation for further research aimed at isolating and characterizing the active compounds responsible for these effects, which could lead to the development of novel and effective anti-cancer drugs.